2020
DOI: 10.1093/milmed/usaa185
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Dose Associated With Military Service: Implications for the Clinical Management of Inherited Risk for Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Introduction High levels of aerobic exercise in individuals who have a gene mutation associated with arrhythmogenic right ventricular cardiomyopathy (ARVC) are associated with clinical disease progression. Guidelines consequently restrict patients from competitive athletics. However, there is minimal literature to guide the safe dosing of physical activity outside of the setting of competitive athletics. Patients may be physically active pursuant to a variety of careers, including military se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The Medical Subject Headings (MeSH) terms used and combined were “Arrhythmogenic Right Ventricular Dysplasia” [Mesh] AND “Exercise” [Mesh], which resulted in 72 records. Seven animal or preclinical[ 15 16 17 18 19 20 21 ] and 18 clinical studies[ 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] were selected and discussed. [ Table 1 ] presents the definitions of terms used in the identified studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Medical Subject Headings (MeSH) terms used and combined were “Arrhythmogenic Right Ventricular Dysplasia” [Mesh] AND “Exercise” [Mesh], which resulted in 72 records. Seven animal or preclinical[ 15 16 17 18 19 20 21 ] and 18 clinical studies[ 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] were selected and discussed. [ Table 1 ] presents the definitions of terms used in the identified studies.…”
Section: Methodsmentioning
confidence: 99%
“…[ Table 1 ] presents the definitions of terms used in the identified studies. [ 22 23 25 26 27 28 29 30 32 33 36 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Segre et al. [20] reported that activity below 700-1100 MET-hours/year is not associated with poor clinical outcomes for gene-positive individuals. Those studies show that low to moderate levels of physical activity may not be detrimental to patient's health and prognosis and they should not be completely deprived of the benefits of exercise.…”
Section: Role Of Physical Activitymentioning
confidence: 97%